Pulmonary Embolism: A Narrative Literature Review - Bobby Hasibuan; Oea Khairsyaf; Fenty Anggrainy (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2022)
Pulmonary embolism (PE) is a pulmonary emergency that is quite common with various clinical manifestations, from asymptomatic to life-threatening. The incidence of pulmonary embolism is reported to be 1 per 1000 population, with 50,000 deaths per year. Making the diagnosis is difficult because the symptoms vary widely in each patient. Management of acute pulmonary embolism is carried out with a systematic approach involving early intervention, patient risk stratification, selection of therapy, and determination of the length of treatment.